2016
DOI: 10.4103/0973-1482.151443
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative verrucous leukoplakia: An update

Abstract: Proliferative verrucous leukoplakia (PVL) is a rare form of oral leukoplakia, which was first described in 1985 by Hansen et al. Since then, various published case series have presented PVL as a disease with aggressive biological behavior due to its high probability of recurrence and a high rate of malignant transformation, usually higher than 70%. PVL is a long-term progressive condition, which is observed more frequently in elderly women, over 60 years at the time of diagnosis. The buccal mucosa and tongue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 0 publications
0
28
0
7
Order By: Relevance
“…Current evidence indicates a higher frequency in older females (>60 years of age), with the gingiva being the most commonly involved site, followed by the buccal mucosa and the tongue. 81,[84][85][86] Gingival and palatal lesions are also the most likely to undergo malignant transformation. 84,87,88 The etiopathogenesis is poorly understood, and there appears to be no correlation with alcohol consumption, tobacco chewing, smoking, or HPV infection.…”
Section: Proliferative Verrucous Leukoplakiamentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence indicates a higher frequency in older females (>60 years of age), with the gingiva being the most commonly involved site, followed by the buccal mucosa and the tongue. 81,[84][85][86] Gingival and palatal lesions are also the most likely to undergo malignant transformation. 84,87,88 The etiopathogenesis is poorly understood, and there appears to be no correlation with alcohol consumption, tobacco chewing, smoking, or HPV infection.…”
Section: Proliferative Verrucous Leukoplakiamentioning
confidence: 99%
“…84,87,88 The etiopathogenesis is poorly understood, and there appears to be no correlation with alcohol consumption, tobacco chewing, smoking, or HPV infection. 81,84,85 The overall mortality rate is also somewhat unclear, with some studies reporting a 5-year survival rate of 60%, whereas others have suggested it to be less aggressive. In their review, Pentenero et al 84 estimated an overall mortality rate of 30%.…”
Section: Proliferative Verrucous Leukoplakiamentioning
confidence: 99%
“…The mean age of patients with long-lasting lesions of PVL was reported over 60 years [4,5,34,37]. While the etiology of this condition is uncertain genetic factors and viral infections such as Human Papilloma Virus especially type 16 and 18 and Epstein-Barr Virus have been proposed [36,37]. Clinical appearance in the early stage contains small whitish and well-defined patches or plaques appearing as focal and homogeneous keratotic lesions (Figure 10).…”
Section: Acquired Lesions That Cannot Be Scraped Off (Without Specmentioning
confidence: 99%
“…The lesions enlarge slowly and constantly over time involving diffuse surfaces of the mucosa. Meanwhile, non-homogeneous multifocal areas with speckled and rough surface might appear in the form of exophytic, wart-like, verrucous, polypoid projections or erythematous features [5,34,36,37]. PVL usually develops bilaterally, which affects the buccal mucosa, gingivae, and alveolar ridges.…”
Section: Acquired Lesions That Cannot Be Scraped Off (Without Specmentioning
confidence: 99%
“…Caso existam diferenças nucleares detectadas entre as LBs e LVPs, essas diferenças podem carregar importantes informações preditivas de transformação para ambas as lesões inclusive, embora isso não será uma questão a ser respondida com esse trabalho. Além disso, pelo fato de a LB ser a DBPM mais comum da cavidade bucal, o impacto que um modelo preditivo que ajude diferenciá-la de uma LVP será de grande importância, pois cada lesão apresenta uma abordagem terapêutica específica e riscos distintos de transformação maligna.Um outro fator importante desse estudo é diagnóstico mais exato de uma LVP, pois na literatura os critérios de diagnóstico são clinicopatológicos, mas dotados de muita subjetividade e com critérios morfológicos muitas vezes difíceis de serem aplicados dada a natureza evolutiva da lesão clinicamente(MUNDE;KARLE, 2016). Como consequência, uma LVP em estágio inicial pode ser confundida com uma LB histologicamente e sem qualquer alteração histológica indicativa de progressão, fazendo com que essa lesão seja frequentemente diagnosticada apenas no estágio avançado, quando os aspectos clinicopatológicos são mais exuberantes.…”
unclassified